TBN improves motor function and prolongs survival in a TDP-43M337V mouse model of ALS. Issue 16 (30th April 2021) - Huang, Chunhui; Li, Jun; Zhang, Guiliang; Lin, Yingqi; Li, Caijuan; Zheng, Xiao; Song, Xichen; Han, Bofeng; Guo, Baojian; Tu, Zhuchi; Zhang, Jun; Sun, Yewei; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) are serious neurodegenerative diseases. Although their pathogenesis is unclear, the abnormal accumulation of TAR DNA-binding protein of 43 kDa (TDP-43) is a pathological feature that exists in almost all patients. Thus far, there is no drug that can cure ALS/FTLD. Tetramethylpyrazine nitrone (TBN) is a derivative of tetramethylapyrazine, derived from the traditional Chinese medicine Ligusticum chuanxiong, which has been widely proven to have therapeutic effects on models of various neurodegenerative diseases. TBN is currently under clinical investigation for several indications including a Phase II trial of ALS. Here, we explored the therapeutic effect of TBN in an ALS/FTLD mouse model. We injected the TDP-43 M337V virus into the striatum of mice unilaterally and bilaterally, and then administered 30 mg/kg TBN intragastrically to observe changes in behavior and survival rate of mice. The results showed that in mice with unilateral injection of TDP-43 M337V into the striatum, TBN improved motor deficits and cognitive impairment in the early stages of disease progression. In mice with bilateral injection of TDP-43 M337V into the striatum, TBN not only improved motor function but also prolonged survival rate. Moreover, we show that its therapeutic effect may be through activation of the Akt/mTOR/GSK-3β and AMPK/PGC-1α/Nrf2 signaling pathways. In summary, TBN is a promising agent for the treatment of ALS/FTLD.